2014
DOI: 10.1007/s00726-014-1719-x
|View full text |Cite
|
Sign up to set email alerts
|

Detyrosinated Glu-tubulin is a substrate for cellular Factor XIIIA transglutaminase in differentiating osteoblasts

Abstract: Microtubule components α- and β-tubulin undergo a number of posttranslational modifications that modulate their dynamics and cellular functions. These modifications include polyamination and covalent crosslinking by transglutaminase enzymes. We have demonstrated previously that the less dynamic and more stable tubulin form-detyrosinated Glu-tubulin-is found in high molecular weight, oligomeric complexes in bone-forming osteoblasts during differentiation and along with deposition of collagenous extracellular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
3
8
0
Order By: Relevance
“…Studies have shown that microtubules regulate the expansion of podosome clusters into a belt and that thus disruption of the microtubule network can result in the loss of podosome belt (Destaing et al, ; Destaing, Saltel, Geminard, Jurdic, & Bard, ). Furthermore, previous studies showed that Exoenzyme C3 increased the acetylated α‐tubulin level in osteoclasts (Destaing et al, ), and our group has shown that NC9 regulates detyrosinated Glu‐tubulin in osteoblasts (Al‐Jallad et al, ; Wang, Cui, Hitomi, & Kaartinen, ). Examination of microtubule architecture in osteoclast after NC9 treatment for 24 hr, however, showed no major alterations (Supplementary Figure S4b) and western blotting analysis confirmed that NC9 and Exoenzyme C3 had no effect on the acetylation or detyrosination of α‐tubulin in osteoclasts (Supplementary Figure S4c).…”
Section: Resultsmentioning
confidence: 66%
“…Studies have shown that microtubules regulate the expansion of podosome clusters into a belt and that thus disruption of the microtubule network can result in the loss of podosome belt (Destaing et al, ; Destaing, Saltel, Geminard, Jurdic, & Bard, ). Furthermore, previous studies showed that Exoenzyme C3 increased the acetylated α‐tubulin level in osteoclasts (Destaing et al, ), and our group has shown that NC9 regulates detyrosinated Glu‐tubulin in osteoblasts (Al‐Jallad et al, ; Wang, Cui, Hitomi, & Kaartinen, ). Examination of microtubule architecture in osteoclast after NC9 treatment for 24 hr, however, showed no major alterations (Supplementary Figure S4b) and western blotting analysis confirmed that NC9 and Exoenzyme C3 had no effect on the acetylation or detyrosination of α‐tubulin in osteoclasts (Supplementary Figure S4c).…”
Section: Resultsmentioning
confidence: 66%
“…bond (isopeptide crosslink/bond) that can induce the formation of multimeric protein networks and change the conformation, structure, solubility, biochemical stability, and cell-adhesion properties of substrate proteins. [23][24][25][26][27][28][29] In addition to fibrin, a major extracellular substrate for FXIII-A is fibronectin (FN). 30 FN is an extracellular glycoprotein capable of regulating various cellular functions, including proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…This matrix forms a scaffold for other proteins to adhere to, including type 1 collagen . Surface‐associated osteoblast FXIII‐A is involved in stabilizing the interaction between microtubules and the plasma membrane, which, in turn, enhances the secretion of collagen . Collagen is the principal component of bone matrix, and it appears that both FXIII‐A activity and fibronectin are essential for normal collagen deposition .…”
Section: Fxiii‐a In Bonementioning
confidence: 99%